Optical and Structural Properties of Prepared Polyaniline – Graphene (PANI/GN) Nanocomposite - Abdullah, Najlaa J.; Essa, Abbas F.; Hasan, Salma M. (Iraqi Journal of Science, 2021)
Polyaniline (PANI) polymer was successfully prepared by the chemical oxidation method at 0 oC. Polyaniline-nano grapheme (GN) powder nanocomposites were prepared by the addition of GN with different weight ratios (0.1, 1, 5, and 10 g wt. %) during the polymerization of PANI. It was found that the polymerization reaction of poly-aniline was exothermic. The effect of adding nano-graphene powder during polymerization process on the time and temperature of the reaction was studied. The resulting polymer was diagnosed using several methods, including Fourier transform infrared spectroscopy (FT-IR) and UV-VIS spectrophotometry. The results of FTIR demonstrated a shift to higher wave numbers in the peaks of nanocomposites, due to PANI peaks, in addition to the matching between the groups of active sites of the polymer with its chemical composition. The results of the optical properties showed a decrease in the energy gap of the nanocomposite compared with that of the pure PANI sample. The morphology of the samples was studied using Scanning Electron Microscope (SEM). The increase in the concentration of GN led to a change in the surface morphology of the composites. The results predict that the PANI/GN nano-composites can be used in many applications, such as those of sensors.